Genetics of pheochromocytoma and paraganglioma syndromes: new advances and future treatment options - Vicha, Ales; Musil, Zdenek; Pacak, Karel (Current opinion in endocrinology, diabetes, and obesity, 2013)
PURPOSE OF REVIEW: To summarize the recent advances in the genetics of pheochromocytoma and paraganglioma (PHEO/PGL), focusing on the new susceptibility genes and dividing PHEOs/PGLs into two groups based on their transcription profile. RECENT FINDINGS: Recently, TMEM127, MYC-associated factor X, and hypoxia-inducible factor (HIF) 2α have been described in the pathogenesis of PHEOs/PGLs. Thus, now about 30-40% of these tumors are linked to the germline mutations, which also include mutations in the VHL, RET, NF1, SDHx, and SDHAF2 genes. Furthermore, PHEOs/PGLs have been divided into two groups, cluster 1 (SDHx/VHL) and cluster 2 (RET/NF1), based on the transcription profile revealed by genome-wide expression microarray analysis. SUMMARY: PHEOs/PGLs are the most inherited tumors among (neuro)endocrine tumors. Future approaches in genetics, including whole-genome sequencing, will allow the discovery of additional PHEO/PGL susceptibility genes. The current division of PHEOs/PGLs into cluster 1 and 2 provides us with additional knowledge related to the pathogenesis of these tumors, including the introduction of new treatment options for patients with metastatic PHEOs/PGLs. New discoveries related to the role of the HIF-1/HIF-2α genes in the pathogenesis of almost all inherited PHEOs/PGLs may call for a new regrouping of these tumors and discoveries of new treatment targets.
Keywords: Paraganglioma; feochromocytom; izoenzymy; Pheochromocytoma; nádorový supresorový protein VHL; mutace; Genetic Predisposition to Disease; Proto-Oncogene Proteins c-ret; Succinate Dehydrogenase; Adrenal Gland Neoplasms; Neurofibromin 1; sukcinátdehydrogenasa; nádory nadledvin; Von Hippel-Lindau Tumor Suppressor Protein; paragangliom; lidé; Humans; protoonkogenní proteiny c-ret; neurofibromin 1; Isoenzymes; Mutation; genetická predispozice k nemoci